A new species of Tragia (Euphorbiaceae) from Oaxaca, Mexico - Gordillo, Martha Martinez; Colín, Rafael Torres (Phytotaxa, 2015)
A new species of Tragia from the state of Oaxaca, Mexico is described and illustrated; it is different from other known Mexican species, although somewhat similar in habit to T. nepetifolia. Tragia chiltepeca is an erect herb with deeply cordate leaves with an acuminate apex and a long petiole, a long pedunculate inflorescence, a single pistillate flower in the proximal node, several male flowers at the distal nodes, and pyriform buds. This species is endemic to the Tuxtepec district. A taxonomic key is provided to distinguish this from other Tragia species in Oaxaca.